PENGARUH MOTIVASI TERHADAP KEMAMPUAN TEKNIK MENYUSUI YANG BENAR PADA IBU NIFAS - Atiul Impartina (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2017)
Parturition period's important given to mother and baby. The case with neonatal period is also a time of crisis of the life of the baby. Based on the data there are parturition who have experiencing ASI dam as much as 37, 12%. ASI dam occurs due to many still mother breastfeeding her baby hasn’t been able to parturition with the correct breastfeeding technique. The purpose of this research is to know influence the giving motivation to ward ability correct breastfeeding technique on childbirth.This research uses pre-experimental design approach with one group pretest-posttest design. The population of the research are all of parturition and the number of samples as much as 15 person. The technique of sampling with the purposive sampling technique. The independent variable is the giving motivation and dependent variable is the correct breastfeeding technique. Data collecting using questionnaires and observation. Analysis of test data using the Wilcoxon sign rank test with asignificance level of p < 0,05. The results of the statistic Z value obtained = -3,494 with p = 0,000 where p < 0,05 then H0 is rejected the means there is influence the giving motivation against the correct breasfeeding technique ability on childbirth. Based on the results of the research are expected grant of motivation on how further enhanced for the health workforce in the technique of feeding the baby.